State Trading in Tendu Leaves in Madhya Pradesh - Shrivastava, S. S.; Choubey, L. K. (Indian Forester, 1968)
Tendu leaves used as wrapper of 'bidi' is an important Forest Produce of Commercial value in Madhya Pradesh. About 22 lakh standard bags of Tendu leaves weighing about 10 lakh Quintals are annually collected in the State. This quantity is about 60% of Total production of the Country. Maximum annual revenue realized by outright sale till the year 1964-65 was Rs. 86.08 lakhs. Increasing smuggling and pilferage of leaves from Government forest by Contractors purchasing leaves from tenancy holdings and continuous exploitation of tenants by these intermediaries prompted Government of M.P. to introduce State Trading in Tendu Leaves by enacting the Madhya Pradesh Tendu Patta (Vyapar Viniyaman) Adhiniyam 1964 and framing rules thereunder. The provisions of the Act and Scheme of working is briefly described. The annual revenue of the State increased to Rs. 222 lakhs in 1965-66 to Rs. 310 lakhs in 1966-67 and expected to touch the figure of Rs. 410 lakhs in 1967-68.